Hubungan Asupan Energi dan Protein dengan Stunting Pada Balita Usia 12-36 Bulan - Sayiati, Nadhifa Qori; Firmansyah, Firmansyah (Fakultas Ilmu Keperawatan Universitas Klabat, 2025)
Asupan gizi merupakan faktor langsung yang menyebabkan stunting pada balita. Asupan gizi dapat diperoleh dari beberapa zat gizi, diantaranya yaitu zat gizi makro seperti energi dan protein. Tujuan dari penelitian ini untuk mengetahui hubungan asupan energi dan protein dengan stunting pada balita usia 12-36 bulan di wilayah kerja Puskesmas Gatak Kabupaten Sukoharjo. Desain penelitian ini menggunakan observasional dengan pendekatan crossectional. Teknik pengambilan sampel menggunakan Proportional Random Sampling dengan banyak sampel 70 balita. Data asupan energi dan protein diperoleh dengan cara wawancara secara langsung Bersama ibu responden menggunakan form Semi-Quantitatif Food Frequency (SQ-FFQ) dan menggunakan indikator tingkat asupan gizi menurut WNPG 2004. Data stunting diperoleh dengan pengukuran tinggi badan dan umur secara langsung dengan menggunakan indikator z-score TB/U menurut Permenkes 2020. Analisis data menggunakan analisis univariat dan bivariat dengan uji Rank Spearman. Hasil didapatkan sebagian besar balita 50% mengalami stunting, 74,3% balita memiliki asupan energi cukup (x̄ = 128 %) dan 60% balita yang memiliki asupan protein cukup (x̄ = 124,44 %). Uji statistik Rank Spearman menunjukkan terdapat hubungan signifikan antara asupan energi dan protein dengan stunting pada balita usia 12-36 bulan (p=0,000). Inadequate nutritional intake over a long period of time is a direct factor that causes stunting in toddlers. Nutritional intake can be obtained from several nutrients, including macronutrients such as energy and protein. The aim of this research was to determine the relationship between energy and protein intake and stunting in toddlers aged 12-36 months in the working area of ​​the Gatak Health Center, Sukoharjo Regency. This research design uses observational with a cross sectional approach. The sampling technique used Proportional Random Sampling with a sample size of 70 toddlers. Energy and protein intake data was obtained by direct interviews with the respondent's mother using the Semi-Quantitative Food Frequency (SQ-FFQ) form and using indicators of nutritional intake levels according to WNPG 2004. Stunting data was obtained by directly measuring height and age using the TB/U z-score indicator according to the 2020 Minister of Health Regulation. Data analysis used univariate and bivariate analysis with the Spearman Rank test. The results showed that the percentage of toddlers who were stunted and those who were not stunted was the same (50%), 74.3% of toddlers had sufficient energy intake (x̄ = 128%) and 60% of toddlers had sufficient protein intake (x̄ = 124.44%). The Spearman Rank statistical test shows that there is a significant relationship between energy and protein intake and stunting in toddlers aged 12-36 months (p=0.000). It is recommended that mothers of toddlers can improve their children's nutritional status by accompanying and monitoring their children's eating patterns, including the frequency and variety of meals. For future researchers, more complex variables and a larger number of samples can be added to find out the factors that influence nutritional problems in toddlers.